Pengaruh Gaya Kepemimpinan Transformasional, Komunikasi Internal dan Budaya Kerja Digital terhadap Kinerja Pegawai pada Dinas Komunikasi dan Informatika Kabupaten Asahan - Muhammad Rinaldi Prawira; Aris Siregar (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Employee performance is an important factor in supporting the effectiveness of public service delivery, especially in government institutions facing digital transformation challenges. However, employee performance can be influenced by several organizational factors, including transformational leadership, internal communication, and digital work culture. This study aims to analyze the partial and simultaneous effects of transformational leadership style, internal communication, and digital work culture on employee performance at the Communication and Informatics Office of Asahan Regency. The research applied a quantitative descriptive approach using a saturated sampling technique involving 41 employees as respondents. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of IBM SPSS 20. The results indicate that transformational leadership style has a positive and significant effect on employee performance with a t-value of 2.648. Internal communication also shows a significant positive effect with a t-value of 2.300, while digital work culture has the strongest influence with a t-value of 4.201. Simultaneously, the three independent variables significantly affect employee performance, as indicated by an F-value of 18.392. The coefficient of determination shows that 56.6% of employee performance is explained by transformational leadership, internal communication, and digital work culture.